Prophetic Strategy Against Hoaxes and Hypocrisy: The Case of Abdullah bin Ubay— Lessons for Modern Leadership and Ethical Communication - Ahmad Dhiyaul Haq bin Mahsyar; St. Nurhayati; Mahsyar; Elihamid (FAKULTAS DAKWAH UIN SALATIGA, 2025)
The leadership of Prophet Muhammad (peace be upon him) in Medina faced significant internal challenges, notably from Abdullah bin Ubay, a key figure known for his hypocrisy and efforts to destabilize the Muslim community. His actions, including slander, hoaxes, and provocations, posed serious threats to the unity and progress of Islamic da'wah during its formative years. This study investigates the impact of Abdullah bin Ubay’s negative communications and the strategic responses of the Prophet between the 2nd and 9th years of Hijrah. Using a qualitative, library-based research method and a political-historical lens, the study identifies two main types of messages from Abdullah bin Ubay: verbal and non-verbal. Verbal attacks included slander, such as the false accusations during the Battle of Banu Mustaliq and the incident involving Aisyah and Shafwan bin al-Mu’attal. Non-verbal provocations included actions like troop withdrawal during the Battle of Uhud, intended to weaken morale and sow division. In response, Prophet Muhammad employed a set of wise and strategic communication methods. He showed patience, avoided public confrontation, and entrusted inner intentions to Allah’s judgment. He used reasoned dialogue, refrained from punitive actions like leading Ubay’s funeral prayer, and chose reconciliation over retaliation. The Prophet also promoted consultation, verified information, and practiced direct clarification to counter hoaxes. The study concludes that the Prophet’s approach reflects a profound balance of spiritual integrity, political wisdom, and social resilience, offering enduring lessons in leadership, conflict resolution, and ethical communication